Social Capital and Enterprise in the Modern State (Springer International Publishing, 2018)
Given the global crises confronting the world today, it is important to interrogate the notion of "the modern state" and to evaluate its effectiveness in providing security and services for its populations, including the most disadvantaged and vulnerable. This book investigates the modern state's capacity to serve its constituents by examining the organisations that facilitate two key elements of contemporary living: social capital and social enterprise. These elements are explored in a series of rich case studies located in Australia, Ireland and Bangladesh, with broader implications for policy and practice in the rest of the world. The case studies highlight the growing importance of social enterprise and social entrepreneurship in fostering social capital and in contributing to the idea of "the enabling state". This book will appeal to researchers, policy-makers and community leaders working in business, education, employment pathways, homelessness, housing, local government, mental health, public administration and refugee resettlement. Éidín Ní Shé is Research Scientist - Health Systems in the School of Nursing, Midwifery and Health Systems at University College Dublin, Ireland. Her previous academic and research appointments were at the University of Technology Sydney, the University of Southern Queensland and the University of Melbourne, Australia; and the University of Limerick, Ireland. Lorelle J. Burton is Professor of Psychology in the School of Psychology and Counselling, and Associate Dean (Students) in the Faculty of Health, Engineering and Sciences, at the Toowoomba campus of the University of Southern Queensland, Australia. She is also the Independent Chair of the Headspace Toowoomba Consortium. Patrick Alan Danaher is Associate Dean (Research and Research Training) in the Faculty of Business, Education, Law and Arts at the Toowoomba campus of the University of Southern Queensland, Australia. He is also currently an Adjunct Professor in the School of Education and the Arts at CQUniversity, Australia. .